Übergänge in Lebensbiografien und eine (sozial-)pädagogische Perspektivierung - Safiye Yıldız (IUBH Internationale Hochschule, 2020)
– The paper deals with the importance of transition research, for the investigation of problems in life-biographical transitions as well as for a critically-reflexive transition-oriented (social)pedagogical work. In this context, considerations from the educational sciences and sociology on transitions are looked at and some thoughts on the fundamental necessity of a transition-oriented practice of (social)pedagogical work and for professional action are emphasized. The relevance of actor-network theories and (trans-)migration studies perspectives for transition research will also be addressed.
Keywords: 300; life-biographical; transition research; actor-network theories; trans-migration studies perspectives; critically-reflexive transition-oriented (social) pedagogical work; Lebens(ver)läufe; Übergangsforschung; Akteur-Netzwerk-Theorien; (Trans-)Migrationsforschung; kritisch-reflexive; übergangsorientierte (sozial-)pädagogische Arbeit